MAGE-A3 immunotherapeutic as adjuvant therapy for patients with resected, MAGE-A3-positive, stage III melanoma (DERMA): a double-blind, randomised, placebo-controlled, phase 3 trial. Issue 7 (July 2018) - Dreno, Brigitte; Thompson, John F; Smithers, Bernard Mark; Santinami, Mario; Jouary, Thomas; Gutzmer, Ralf; Levchenko, Evgeny; Rutkowski, Piotr; Grob, Jean-Jacques; Korovin, Sergii; Drucis, Kamil; Grange, Florent; et al.
Summary: Background: Despite newly approved treatments, metastatic melanoma remains a life-threatening condition. We aimed to evaluate the efficacy of the MAGE-A3 immunotherapeutic in patients with stage IIIB or IIIC melanoma in the adjuvant setting. Methods: DERMA was a phase 3, double-blind, randomised, placebo-controlled trial done in 31 countries and 263 centres. Eligible patients were 18 years or older and had histologically proven, completely resected, stage IIIB or IIIC, MAGE-A3-positive cutaneous melanoma with macroscopic lymph node involvement and an Eastern Cooperative Oncology Group performance score of 0 or 1. Randomisation and treatment allocation at the investigator sites were done centrally via the internet. We randomly assigned patients (2:1) to receive up to 13 intramuscular injections of recombinant MAGE-A3 with AS15 immunostimulant (MAGE-A3 immunotherapeutic; 300 μg MAGE-A3 antigen plus 420 μg CpG 7909 reconstituted in AS01B to a total volume of 0·5 mL), or placebo, over a 27-month period: five doses at 3-weekly intervals, followed by eight doses at 12-weekly intervals. The co-primary outcomes were disease-free survival in the overall population and in patients with a potentially predictive gene signature (GS-positive) identified previously and validated here via an adaptive signature design. The final analyses included all patients who had received at least one dose of study treatment; analyses for efficacy were in the as-randomised population and for safety were in the as-treated population. This trial is registered withClinicalTrials.gov, numberNCT00796445 . Findings: Between Dec 1, 2008, and Sept 19, 2011, 3914 patients were screened, 1391 randomly assigned, and 1345 started treatment (n=895 for MAGE-A3 and n=450 for placebo). At final analysis (data cutoff May 23, 2013), median follow-up was 28·0 months [IQR 23·3–35·5] in the MAGE-A3 group and 28·1 months [23·7–36·9] in the placebo group. Median disease-free survival was 11·0 months (95% CI 10·0–11·9) in the MAGE-A3 group and 11·2 months (8·6–14·1) in the placebo group (hazard ratio [HR] 1·01, 0·88–1·17, p=0·86). In the GS-positive population, median disease-free survival was 9·9 months (95% CI 5·7–17·6) in the MAGE-A3 group and 11·6 months (5·6–22·3) in the placebo group (HR 1·11, 0·83–1·49, p=0·48). Within the first 31 days of treatment, adverse events of grade 3 or worse were reported by 126 (14%) of 894 patients in the MAGE-A3 group and 56 (12%) of 450 patients in the placebo group, treatment-related adverse events of grade 3 or worse by 36 (4%) patients given MAGE-A3 vs six (1%) patients given placebo, and at least one serious adverse event by 14% of patients in both groups (129 patients given MAGE-A3 and 64 patients given placebo). The most common adverse events of grade 3 or worse were neoplasms (33 [4%] patients in the MAGE-A3 group vs 17 [4%] patients in the placebo group), general disorders and administration site conditions (25 [3%] for MAGE-A3 vs four [<1%] for placebo) and infections and infestations (17 [2%] for MAGE-A3 vs seven [2%] for placebo). No deaths were related to treatment. Interpretation: An antigen-specific immunotherapeutic alone was not efficacious in this clinical setting. Based on these findings, development of the MAGE-A3 immunotherapeutic for use in melanoma has been stopped. Funding: GlaxoSmithKline Biologicals SA.